Correlation of Lyme Disease–Associated IgG4 Autoantibodies With Synovial Pathology in Antibiotic‐Refractory Lyme Arthritis. Issue 11 (24th September 2018) - Sulka, Katherine B.; Strle, Klemen; Crowley, Jameson T.; Lochhead, Robert B.; Anthony, Robert; Steere, Allen C.
Abstract : Objective: To determine whether IgG subclasses of Borrelia burgdorferi antibodies differ from those of 3 Lyme disease (LD)–associated autoantibodies. Methods: IgG antibody subclasses were determined by enzyme‐linked immunosorbent assay in serum samples from 215 patients with features representative of each of the 3 stages of LD. Antibody and cytokine profiles were measured in matched serum and synovial fluid (SF) samples from patients with Lyme arthritis. Synovial tissue from patients with antibiotic‐refractory arthritis was examined for histologic features, IgG subclasses of plasma cells, and messenger RNA (mRNA) subclass expression. Results: B burgdorferi antibodies were primarily of the IgG1 and IgG3 subclasses, and the levels increased as the infection progressed. In contrast, LD‐associated autoantibodies were mainly of the IgG2 and IgG4 subclasses, and these responses were found primarily in patients with either antibiotic‐refractory or antibiotic‐responsive arthritis, particularly in SF. However, compared with the responsive group, the inflammatory milieu in SF in the refractory group was enriched for cytokines representative of innate, Th1, Th2, and Th17 responses. Synovial tissue in a subgroup of patients with refractory arthritis showed marked expression of mRNA for IgG4 antibodies and large numbers of IgG4‐staining plasma cells. IgG4 autoantibodies in SF to each of the 3 LD‐associated autoantigens correlated with the magnitude of obliterative microvascular lesions and fibrosis in the tissue. Conclusion: Our findings indicate that the subclasses of IgG antibodies to B burgdorferi differ from those of LD‐associated autoantibodies. Furthermore, the correlation of IgG4 autoantibodies with specific synovial pathology in the refractory group suggests a role for these autoantibodies, either protective or pathologic, in antibiotic‐refractory Lyme arthritis.